Bis-(S-benzyl-β-N-(6-methylpyrid-2-yl)methylenedithiocarbazato) nickel(II). - Ravoof, Thahira Begum S A; Omar, Siti Aminah; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne (International Union of crystallography, 2012)
The asymmetric unit of the title compound, [Ni(C15H 14N3S2)2], consists of two independent molecules with similar configurations. Each Ni2+ cation is coordinated in a cis-mode by two tridentate N,N′,S-chelating Schiff base ligands, creating a distorted octa-hedron [the smallest angle being 77.57 (7)° and the widest being 168.97 (7)° for one molecule, and 78.04 (7) and 167.55 (7)° for the second molecule]. The dihedral angle between the mean coordination planes of the two ligands is 86.76 (7)° for one and 89.99 (7)° for the second molecule. π-π inter-actions between neighbouring pyridine rings with plane-to-plane distances of 3.540 (1) and 3.704 (1) Å are observed.